Climbing Fiber Activation Induced by Footshock in the Cerebellar Vermis Lobule IV/V of Freely Moving Mice - Xue, R; Tang, X; Tang, J; Zhang, S; Liao, X; Chen, X; Li, L; Li, X (Physiological research, 2024)
Parallel fibers (PFs) in the cerebellar cortex are involved in a series of coordinated responses in the fear conditioning paradigm induced by footshock. However, whether footshock can activate cerebellar climbing fibers (CFs) remains unclear. In this study, we recorded calcium (Ca2+) activity in CFs by optical fiber photometry in the cerebellar vermis lobule IV/V of freely moving mice with footshock stimulation. We found that the activation of CFs in the lobule IV/V was highly correlated with footshock stimulation but not with the sound stimulation used as a control. This result suggests that afferent information from CFs might be associated with the motor initiation of fear-related behaviors or fear emotion itself. Thus, our results suggest that a characteristic CF signal in the cerebellar cortex might be related to fear processing or footshock-related behaviors (such as startle responses or pain sensation).
Keywords: myši inbrední C57BL; Cerebellum; Cerebellar Cortex; myši; mozeček; Mice, Inbred C57BL; kůra mozečku; Male; elektrický šok; Animals; Mice; Fear; mužské pohlaví; strach; zvířata; Electroshock